Commutativity theorems in rings with involution. Issue 2 (1st February 2017) - Nejjar, B.; Kacha, A.; Mamouni, A.; Oukhtite, L.
ABSTRACT: In this paper, we investigate commutativity of ring R with involution ∗ which admits a derivation satisfying certain algebraic identities. Some well-known results characterizing commutativity of prime rings have been generalized. Finally, we provide examples to show that various restrictions imposed in the hypotheses of our theorems are not superfluous.